The Application of Integrative Education Concept Between Theology and Science For Improving the Quality of Students' Personality at The 12th Grade of SMA Ta'allumul Huda Bumiayu - Ihsan, Khoirul (International Conference of Moslem Society, 2019)
This study was conducted in response to the low capacity of the learners in implementing theology and science. It is to be applied by learners in the school environment and the community in everyday life. Integrative education is an education that combines the truths of revelation with the evidence found in the universe. It said the structure of integrative science, the science merged into a science that is identical, such as character, style, nature. Between the sciences integrated in the unity of material-spiritual dimension, reason-revelation, general science-theology, physical-spiritual world and the hereafter. The design of the study is a qualitative approach and the method used is comparative studies. The data collection both qualitative and quantitative data that will be concluded. In order to know that students are able to apply theology and able to master science. Lately often expressed that the gist of science must be revised in order to reflect its essence and in its application does not lead to great sacrifice. The essence of which can be absorbed by the intellect (lustrous, conscience or subjective sense). Can coordinate all branches of science, that science does not lead to disaster, and that every branch of science that is not regarded as the most important. The goal is to be able to combine two things that is still treated as a dichotomous against both of which resulted in the separation of theology with science. Hence the need for habituation in everyday life. Habits that have been created by students in the school will enhance the theology and science can further improve the quality of students' personality.